Sustainable business model strategy for resilience among pisciculture firms in Thailand - Kittichai Rajchamaha; Montiean Pornparnomchai; Kridtaphob Vorrakkatham; Chakrit Pichyangkul; Burim Otakanon; Parmapon Raungpaka; Peerasut Bunkaewsuk; Wuthikorn Wajarothai; Titipon Boonlertvanit; Angkrit Saengpradab (International Journal of Agricultural Sustainability)
This study investigated the pisciculture sector of start-ups in Thailand to determine factors of the novelty farming resilience model that promote the adoption of a sustainable business model strategy through innovation approach to improve the sector. Employing a qualitative research method, primary data were collected from 109 respondents, including start-ups, customers, regulators, and experts. Furthermore, secondary data were gathered from relevant sources. Through thematic and direct content analysis, this study identified the novelty of business model strategy that has been applied effectively to a relationship between start-ups’ awareness and their adoption of incremental innovations. This reveals that start-ups are most likely to adopt technology if they understand its contribution to farming. Moreover, they are likely to cooperate with stakeholders promoting said technology if they recognize its influence on farming. We also identified challenges in adopting a sustainable business model in the Thai pisciculture sector. The current study highlights strategies that support new knowledge sharing, help start-ups realize new ways to create innovations, and promote sustainable businesses.